An experimental study to characterize the role of multihole nozzle in adjuvant assisted cryospray - Srivastava, Prashant (Elsevier Masson s.r.l., 2023)
Cryospray is a process of skin cancer treatment in which liquid nitrogen is sprayed on the lesion to achieve necrosis. In order to achieve necrosis through cryospray, a combination of particular cooling rate and lethal temperature is required. The small aperture of single hole nozzle (SHN) and the less mass flow rate associated with it reduce the rate of heat transfer from the lesion. Moreover, the low thermal conductivity of lesion further reduces the rate of energy diffusion inside it. These limitations associated with the existing method of cryospray fail to provide complete necrosis in the lesions of size larger than 15 mm in diameter. The present study addresses these issues through the modification in the existing spraying technique, i.e. inclusion of multihole nozzle (MHN) in cryospray and administration of Magnesium Oxide (MgO) nanoparticles as an adjuvant in the lesion to increase its rate of energy diffusion. The influence of mass flow rate and the rate of evaporation of cryogen on cryoablation are analysed experimentally while changing the geometrical parameters of 6 MHNs. To quantify the necrosis, thermocouples and FLIR thermal imaging camera are used to ascertain temperature profile below and above the gel surface respectively. The crystalline nature of nanoparticles is confirmed through TEM and XRD results with a particle diameter ranging between 10 and 40 nm. A comparative study of cryoablation is carried out between nano-phantom and normal-phantom. An increase of 59%, 96% and 64% in the area of necrotic zone is observed on the surface of nano-phantom for MHNs with 5 holes and margin of 1 mm, 1.5 mm and 2 mm respectively. The radius of interacellular ice formation has increased by 5 mm at an axial depth of 2 mm for MHNs with 5 holes in the nano-phantom than that in normal-phantom due to the increase in cooling rate. It is also observed that nano-phantom achieves a lower end temperature than the normal-phantom at every thermocouple position. Among the 6 MHNs selected for the study, MHN with 5 holes and 1.5 mm margin provides the most optimised result with the ablation zone of 42 mm on the surface of gel. Thus, it can be concluded that because of the introduction of adjuvant and modification in spraying device, cryoablation outcomes have been improved both quantitatively and qualitatively. The proposed approach will increase the scope of cryospray in the treatment of larger lesions.
Keywords: Normal-phantom; Multihole nozzle; Adjuvant